PHYSICOCHEMICAL AND PHOTOCATALYTIC STUDIES OF ZNO-SUPPORTED INDONESIAN KAOLINITE (ZNO/KAOLINITE) FOR METHYL VIOLET PHOTOOXIDATION - Endah Desiyani; Fitriani Harjati; Is Fatimah (Khazanah: Jurnal Mahasiswa, 2020)
Research on preparation of photocatalyst of zno-supported onto Indonesian Kaolinite (ZnO/Kaolinite) and photocatalytic activity for methyl violet photo-oxidation has been conducted. ZnO/Kaolinite was prepared by impregnation method utilizing zinc acetate as ZnO precursor and kaolinite sample obtained from Bangka Belitung province, Indonesia. Physicochemical study of the photocatalyst was conducted by x-ray diffraction (XRD), gas sorption analyzer and scanning electrone microscope-energy dispersive x-ray (SEMEDX). Furthermore, photocatalytic activity of the material was evaluated in a bacth photooxidation system of methyl violet degradation. The results showed that prepared ZnO/Kaolinite demonstrated superior and high stable photocatalytic performance in the photooxidation system. The prepared ZnO/Kaolinite is a simply prepared, recovered and reused for advance application of dye wastewater treatment.